Murilla Gorilla and the missing mop - Lloyd, Jennifer (Lloyd, Jennifer. Murilla Gorilla., 2018)
It's a hot afternoon and Murilla Gorilla the Jungle Detective is back on the case. This time, one of Mandrill's mops has disappeared. Will Murilla be able to help her friend out of this sticky mess? Or will she get distracted by thoughts of a cool glass of lemonade?